The extended leisure experiences of music scene participation. Issue 4 (2nd October 2017) - Harmon, Justin; Scott, David
ABSTRACT: Scott and Harmon coined the term extended leisure experiences (ELEs) to describe 'activities that participants engage in following a primary leisure activity'. In this study, we set out to elucidate the ELE of fan participation in the music scene of Jerry Joseph & the Jackmormons. Results were gleaned from an ethnography that focused on the meaning of participation among the band's most dedicated fans. Our findings indicate that ELEs (e.g. listening to and discussing past concerts with other fans) provide participants a temporal venue for understanding their relationship to the band and its music, and building community with other fans. Indeed, the lived experiences of music scene participation are not ephemeral events that evaporate with the passage of time but provide a foundation from which fans embody their experiences and create opportunities to extend aspects of their identity and affiliation through music.